2007
DOI: 10.1007/s10562-007-9357-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Ce1−x Ni x O2 Catalysts for Propane Oxidative Steam Reforming

Abstract: The catalytic activity of Ce 1-x Ni x O 2 samples (x = 0.05; 0.10; 0.20) prepared by combustion synthesis have been evaluated in the Oxidative Steam Reforming of C 3 H 8 . The high activity and stability of Ce 0.95 Ni 0.05 O 2 and Ce 0.90 Ni 0.10 O 2 samples was ascribed to the co-existence of different Ni species: metallic, NiO highly dispersed and Ni 2+ ions incorporated into CeO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The principal role of ceria was connected with the ability to increase the adsorption of steam by its vacant oxygen and to transfer oxygen to the supported metallic site, keeping the surface relatively free of carbon. This self-decoking capability of ceria-based catalysts, due to the gasification reaction by oxygen species from the lattice, was previously studied and discussed by other authors [52][53][54][55] and also in our previous papers [34,36,40,56,57]. In addition, partial incorporation of Pt ions into the ceria matrix to form Pt-Ce solid solution (as revealed from XRD and TPR analysis) enhanced oxygen mobility by increasing CeO 2 structural defects.…”
Section: Time-on-stream Experimentsmentioning
confidence: 57%
“…The principal role of ceria was connected with the ability to increase the adsorption of steam by its vacant oxygen and to transfer oxygen to the supported metallic site, keeping the surface relatively free of carbon. This self-decoking capability of ceria-based catalysts, due to the gasification reaction by oxygen species from the lattice, was previously studied and discussed by other authors [52][53][54][55] and also in our previous papers [34,36,40,56,57]. In addition, partial incorporation of Pt ions into the ceria matrix to form Pt-Ce solid solution (as revealed from XRD and TPR analysis) enhanced oxygen mobility by increasing CeO 2 structural defects.…”
Section: Time-on-stream Experimentsmentioning
confidence: 57%
“…Interestingly, two overlapping reduction peaks centered at lower temperatures (245 and 280 • C) were also observed. The first peak at 245 • C can be attributed to the reduction of O 2 molecules possibly adsorbed on surface oxygen (O) vacancies [26,34]; as discussed in Section 3.1, the incorporation of Ni species into the ceria lattice usually generates O vacancies that can easily adsorb O 2 molecules, which in turn can be easily reduced by H 2 at lower temperatures. The second peak located at 280 • C corresponds to the reduction of Ni species present into the CeO 2 lattice [26].…”
Section: Temperature Programmed Reduction (Tpr) Studiesmentioning
confidence: 99%
“…These weaker (active) adsorbates are reduced by H 2 at lower temperatures. The b peak can be attributed to the reduction of lattice coordinated NiO species and the surface/subsurface oxygen species of ceria [8,11]. It suggests that there is a certain synergistic interaction between Ni-O and Ce-O.…”
Section: Raman Analysismentioning
confidence: 99%
“…By utilizing the oxygen buffering effect, CeO 2 -NiO catalysts show merits for hydrogenation and oxidation [7][8][9][10][11]. Moreover, it has been shown that the nanostructures, redox properties, and oxygen storage capacities of ceria-based materials can influence the morphology and electronic properties of the loaded metals.…”
Section: Introductionmentioning
confidence: 99%